Korelasi Kadar Glukosa Darah Dengan Nilai ABI Pada Diabetes Melitus Tipe II - Silaban, Riwanti; AZ, Rasyidah; Astuti, Ani (Universitas Fort De Kock Bukittinggi, 2021)
Background: Diabetes is a group of metabolic disease characterized by increased glucose levels in the blood caused by the secretion of insulin . Methods: This research is a quantitative study with a correlation study approach. This research was conducted on 02-29 August 2020. The samples in this study were as many as 40 people taken with purposive sampling techniques. Data collection by measuring blood sugar levels of DM Type II patients and Ankle Brachial Index (ABI) values. Data analyzed univariate and bivariate using spearman rank test. Results: The results showed from 40 respondents, blood sugar levels were unstable as many as 21 respondents (52.5%) and normal category ABI scores of 23 respondents (57.5%). No choleration of blood glucose levels with Ankle Brachial Index (ABI) of diabetes mellitus type II patients with a value of p = 0.053 > 0.05. Conclusion: The results showed from 40 respondents, blood sugar levels were unstable as many as 21 respondents (52.5%) and normal category ABI scores of 23 respondents (57.5%). No choleration of blood glucose levels with Ankle Brachial Index (ABI) of diabetes mellitus type II patients with a value of p = 0.053 > 0.05. Keywords: Blood sugar levels, ABI, Diabetes Mellitus